Bean transformation in Africa: where are we and where are we going? - Nchanji, Eileen Bogweh (Pan-Africa Bean Research Alliance, 2018)
Common bean, (Phaseolus vulgaris L.) generally grown as a subsistence crop for home consumption is fast becoming a commercial crop sold by farmers for income. The call for bean transformation comes at a time when the population is increasing and the demand for bean grains and bean products is at its highest, especially as it’s being considered a “poor man's meat”. The Pan-African Bean Alliance (PABRA) is leading this transformation by increasing access to mechanisation, technology, capacity building, credit, markets for men with emphasis on women and youths, thus creating an enabling environment for business.